2009
DOI: 10.1007/s00535-008-2279-1
|View full text |Cite
|
Sign up to set email alerts
|

Portosystemic shunts in a large cohort of patients with liver cirrhosis: detection rate and clinical relevance

Abstract: The left gastric vein is associated with some sonographic and clinical markers of disease severity, whereas the absence of portosystemic collaterals or the presence of paraumbilical veins seems to identify cirrhotics with markers predictive of a more favorable clinical course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 31 publications
1
59
2
Order By: Relevance
“…In portal hypertension conditions, the intestinal recruitment of leucocytes is delayed, the local immune response may not be able to prevent the passage of bacteria from intestinal lumen to the systemic circulation, and mesenteric lymph nodes are deranged to retain and destroy bacteria [10][11][12]. The logical consequence is that endotoxin or bacterial DNA may easily reach the systemic circulation, causing liver endothelial dysfunction, imbalance of the intrahepatic circulation, worsening of portal hypertension, and hemodynamic complications, as those observed in studies on cirrhotics in normal conditions and post-prandial phase [13][14][15].…”
Section: Pathophysiologymentioning
confidence: 99%
“…In portal hypertension conditions, the intestinal recruitment of leucocytes is delayed, the local immune response may not be able to prevent the passage of bacteria from intestinal lumen to the systemic circulation, and mesenteric lymph nodes are deranged to retain and destroy bacteria [10][11][12]. The logical consequence is that endotoxin or bacterial DNA may easily reach the systemic circulation, causing liver endothelial dysfunction, imbalance of the intrahepatic circulation, worsening of portal hypertension, and hemodynamic complications, as those observed in studies on cirrhotics in normal conditions and post-prandial phase [13][14][15].…”
Section: Pathophysiologymentioning
confidence: 99%
“…3,4,5). After the Valsalva maneuver was discontinued, color flow mapping of the left renal veins became indistinct, reflecting decreased antegrade blood flow.…”
Section: Resultsmentioning
confidence: 96%
“…Spleno-renal shunt is one of the large spontaneous shunt paths that forms in the splenic hilum and is present in from nearly 14% to up to 21% of patients with hepatic cirrhosis [3]. Spleno-renal shunt is depicted on ultrasound as a blood vessel that meanders near the splenic hilum.…”
Section: Introductionmentioning
confidence: 99%
“…According to the guidelines of the European Society of Gastrointestinal Endoscopy [21], CE is currently the first-line imaging modality for diagnosing small-bowel lesions [22-24], especially for patients with OGIB. In addition, CE is usually preferred over DBE, as it is a safe and minimally invasive procedure, with the capsule being easy to swallow; yet its detection capabilities are extensive, such that small lesions, such as an angioectasia of the small bowel, can be diagnosed [25, 26]. We previously reported that CE has the potential to be used as a screening method to detect lesions related to PHT, as well as being effective for the diagnosis of EVs and PHG in patients with LC [2].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PSs develop in an environment where the portal pressure is >10 mm Hg, acting as a bypass to compensate for PHT. Therefore, the presence of PSs indicates the severity of PHT and the exacerbation of EVs [26, 32]. …”
Section: Discussionmentioning
confidence: 99%